High-strength room-temperature vulcanized fluorosilicone sealant, fluorosilicone cross-linking agent and preparation and application of high-strength room-temperature vulcanized fluorosilicone sealant

By using trifluoropropyl-containing acyloxysilane oligomer as a cross-linking agent in the fluorosilicone sealant, and combining it with high and low viscosity hydroxyl fluorosilicone oil and a tackifier, the problem of existing fluorosilicone sealants is solved. Fluorosilicone sealants with high strength and excellent oil resistance have been realized due to deficiencies in high strength and oil resistance.

CN119350384AActive Publication Date: 2025-01-24NEWERA CHEM SHANDONG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411470783.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing fluorosilic sealants have shortcomings in high strength and oil resistance, especially in applications in aviation and internal combustion engines, which are difficult to meet the requirements of high strength, high adhesion and degradation resistance.

Method used

The lycosilic oblimrophrophic polymer containing trifluoropate is used as a fluorine silicon intercourse. It improves the mechanical properties and oil resistance of the sealing agent through a well -compatibleizedly compatible gum oxidation response to the fluorine silicon system. At the same time, through the complexity of high and low viscosity hydroxyl fluorine silicone oil and the use of adhesives, the cross -linking network system of sealing agents is improved, and its mechanical properties and adhesion performance are improved.

Benefits of technology

The preparation of high-intensity room temperature sulfurized sulfurizer sealing agent has excellent oil resistance and adhesion performance. It can be used for a long time in the range of -60 to 250 ° C, which is suitable for the sealing application of aviation engines and overall fuel tanks of the aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350384A_ABST
    Figure CN119350384A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength room-temperature vulcanized fluorosilicone sealant, a fluorosilicone cross-linking agent as well as preparation and application of the high-strength room-temperature vulcanized fluorosilicone sealant and the fluorosilicone cross-linking agent. The fluorosilicone cross-linking agent is an acyloxy silane oligomer containing trifluoropropyl. The fluorosilicone sealant comprises the following components in parts by weight: 100 parts of hydroxyl fluorosilicone oil I; 20 to 30 parts of fumed silica; 10 to 20 parts of gas phase method titanium dioxide; 3 to 10 parts of hydroxyl fluorosilicone oil II; 5 to 10 parts of methyl fluorosilicone oil; 5 to 10 parts of a fluorosilicone cross-linking agent; 1 to 3 parts of a tackifier; and 0.01 to 0.5 part of a catalyst. The fluorosilicone cross-linking agent disclosed by the invention can be well compatible with a fluorosilicone system, the cross-linked network system of the fluorosilicone sealant is remarkably improved by compounding the high-viscosity hydroxyl fluorosilicone oil and the low-viscosity hydroxyl fluorosilicone oil for use, and fluorosilicone materials with different structures are mutually matched and have a synergistic effect, so that the fluorosilicone sealant keeps good tolerance to various types of fuel oil and engine oil and has a remarkable oil-resistant effect; the material can be used as an oil-resistant sealing material to be applied to multiple fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber materials, and in particular to a high-strength room temperature vulcanized fluorosilicone sealant, a fluorosilicone crosslinking agent, and a preparation method and use thereof. Background Art

[0002] Fluorosilicone sealant is also called single-component room temperature vulcanized fluorosilicone rubber. It is made of α,ω-dihydroxy polytrifluoropropyl methylsiloxane as base rubber and mixed with crosslinking agent, catalyst, filler and other additives under moisture-proof conditions. It is squeezed out of the packaging tube when used and crosslinked and cured by contact with moisture in the air. It has excellent waterproofness and airtightness, resistance to a variety of chemical reagents and oils, good bonding performance to most substrates, and can be used for a long time in the range of -60 to 250℃. It is used for assembly and repair of parts that cannot be welded, such as small and irregular grooves, slots, seams and other parts. It is used as in-situ molding sealing materials for automobiles and various machinery, bonding materials for electronic components, especially for sealing, caulking and potting of aircraft engines and aircraft integral fuel tanks, to meet the use requirements of aviation equipment.

[0003] In recent years, with the rapid development of the aviation industry and internal combustion engine technology, the sealing materials used are required to have not only good temperature resistance and oil resistance, but also high strength, high adhesion and degradation resistance to meet the application requirements of fuel tanks, fuselages and places exposed to fuel and lubricating oil. Patent document CN102850807A discloses a one-component room temperature vulcanized fluorosilicone rubber and a preparation method thereof, wherein hydroxyl-terminated fluorinated polysiloxane, inorganic filler, crosslinking agent, silane coupling agent, titanate coupling agent, catalyst, etc. are mixed in a high-speed disperser to obtain the crosslinking agent. In the document, conventional silane coupling agents are selected as the crosslinking agent, such as methyl tributanoximosilane, methyl triacetoxysilane, methyl trimethoxysilane, etc. Such coupling agents have poor compatibility with fluorosilicone materials, the system is incompatible, and it is difficult to evenly disperse into the rubber during the mixing process. Moreover, due to the difference in the system, it is difficult to react well with the base rubber, and the effect of using as a crosslinking agent is very poor, and a high-strength fluorosilicone sealant cannot be obtained. Patent document CN105086473A discloses a fluorosilicone sealant for fuel oil solvent resistant parts and its preparation method. First, hydroxyl-terminated fluorosilicone rubber, white carbon black and active nano calcium carbonate are vacuum stirred for 1 hour to prepare a base material, then ethyl orthosilicate, accelerator and catalyst are mixed to prepare an auxiliary agent, and finally a two-component potting glue is prepared in the form of adding 1 part of auxiliary agent to 10 parts of the base material. In this method, the reaction activity of the material is low, the surface drying time is too long, and it is difficult to meet the application requirements in a short time. In addition, the use of the two-component form increases the difficulty of construction. In addition, the strength of the material is low, which cannot meet the high strength requirements of modern industry, and to a certain extent also limits the application of the product.

[0004] Therefore, it is of great practical significance to develop a high-strength fluorosilicone sealant that can be vulcanized at room temperature. Summary of the invention

[0005] In view of the above-mentioned state of the prior art, the inventors of the present invention have conducted in-depth and extensive research in the field of fluorosilicone sealants and found that the use of trifluoropropyl-containing acyloxysilane oligomers as cross-linking agents can be well compatible with the fluorosilicone system, avoiding the problem that conventional coupling agents such as methyltriacetoxysilane and vinyltriacetoxysilane are incompatible with the fluorosilicone system as cross-linking agents. In addition, the cross-linking agent has a high reactivity and can undergo an efficient condensation reaction with the terminal hydroxyl groups of the fluorosilicone rubber base during room temperature vulcanization, making the molecular chain segments more thoroughly cross-linked. In addition, the inventors also found that by compounding high and low viscosity hydroxyl fluorosilicone oils, the cross-linked network system of the fluorosilicone sealant can be significantly improved, the material is evenly dispersed in the system, easy to control, and can improve the mechanical properties of the fluorosilicone sealant. The present invention is completed based on the above-mentioned findings.

[0006] Therefore, an object of the present invention is to provide a fluorosilicone crosslinking agent for a fluorosilicone sealant and a preparation method thereof, wherein the crosslinking agent is well compatible with the fluorosilicone system and has high reactivity.

[0007] The second object of the present invention is to provide a high-strength room temperature vulcanized fluorosilicone sealant and a preparation method thereof. The fluorosilicone sealant can be vulcanized at room temperature, maintains good tolerance to various types of fuels, engine oils, etc., has a significant oil resistance effect, and can be used as an oil-resistant sealing material in multiple fields.

[0008] The technical solution for achieving the above-mentioned invention object can be summarized as follows:

[0009] A fluorosilicone crosslinking agent is an acyloxysilane oligomer containing a trifluoropropyl group.

[0010] According to the present invention, preferably, the trifluoropropyl-containing acyloxysilane oligomer has a structure shown in formula (IV):

[0011]

[0012] In formula (IV), x represents the average degree of polymerization, and 1≤x≤3.

[0013] According to the present invention, the preparation method of the above-mentioned fluorosilicone crosslinking agent comprises the following steps:

[0014] Under the protection of inert gas, anhydrous sodium acetate and toluene are stirred and mixed, heated to reflux to remove moisture, and then trifluoropropyltrichlorosilane is added dropwise to the system for acyl oxidation reaction. After the addition is completed, the reaction is continued to be stirred, and then the temperature is lowered, filtered, and the solvent is recovered to obtain a fluorosilicone crosslinking agent with a structure of formula (IV).

[0015] According to the present invention, preferably, the molar ratio of trifluoropropyltrichlorosilane to anhydrous sodium acetate is 1:(3.1-3.3).

[0016] According to the present invention, preferably, the feed mass ratio of anhydrous sodium acetate to toluene is 1:(2.0-4.0).

[0017] According to the present invention, preferably, the time for removing moisture by heating and refluxing is 3 to 6 hours.

[0018] According to the present invention, preferably, the acyl oxidation reaction temperature is 50-60°C.

[0019] According to the present invention, preferably, the conditions for recovering the solvent are a temperature of 40 to 70° C. and a pressure of -0.04 MPa to -0.08 MPa.

[0020] According to the present invention, the trifluoropropyl-containing acyloxysilane oligomer of the structure represented by formula (IV) is used as a fluorosilicone crosslinking agent for the preparation of a room temperature vulcanized fluorosilicone sealant.

[0021] According to the present invention, a high-strength room temperature vulcanized fluorosilicone sealant includes the above-mentioned fluorosilicone crosslinking agent and comprises the following components in parts by weight:

[0022] Hydroxyfluorosilicone oil I, 100 parts;

[0023] Fumed silica, 20-30 parts;

[0024] Fumed titanium dioxide, 10-20 parts;

[0025] Hydroxyfluorosilicone oil II, 3-10 parts;

[0026] Methyl fluorosilicone oil, 5-10 parts;

[0027] Fluorosilicone crosslinking agent, 5-10 parts;

[0028] Thickener, 1 to 3 parts;

[0029] Catalyst, 0.01-0.5 parts;

[0030] The hydroxy fluorosilicone oil I has a viscosity of 50,000 to 100,000 mPa.s and has a structure shown in formula (I):

[0031]

[0032] In formula (I), n represents the average degree of polymerization, 200≤n≤500;

[0033] The hydroxy fluorosilicone oil II has a viscosity of 100 to 150 mPa.s and has a structure shown in formula (II):

[0034]

[0035] In formula (II), m represents the average degree of polymerization, and 1≤m≤6.

[0036] According to the present invention, preferably, the methyl fluorosilicone oil has a viscosity of 100 to 300 mPa.s and has a structure shown in formula (III):

[0037]

[0038] In formula (III), p represents the average degree of polymerization, and 1≤p≤10.

[0039] According to the present invention, preferably, the BET specific surface area of ​​the fumed silica is 175 to 225 m 2 / g.

[0040] According to the present invention, preferably, the BET specific surface area of ​​the vapor phase titanium dioxide is 35 to 65 m 2 / g.

[0041] According to the present invention, preferably, the tackifier is a mixture of tert-butyl alcohol and vinyl triacetoxysilane in a molar ratio of 2:1, obtained by alcoholysis reaction and then removing low molecular weight treatment.

[0042] According to the present invention, preferably, the alcoholysis reaction temperature of the tackifier is 30-40° C., and the alcoholysis reaction time is 2-4 hours.

[0043] According to the present invention, preferably, the conditions for removing low molecular weight treatment of the tackifier are a temperature of 50 to 80° C. and a pressure of -0.09 MPa.

[0044] According to the present invention, preferably, the catalyst is at least one of dibutyltin dilaurate, dibutyltin diacetate, stannous octoate and dioctyltin dilaurate.

[0045] According to the present invention, the preparation method of the above-mentioned high-strength room temperature vulcanized fluorosilicone sealant comprises the following steps:

[0046] (1) Add hydroxy fluorosilicone oil I and part of fumed silica and fumed titanium dioxide into a vacuum kneader for kneading and mixing, then add hydroxy fluorosilicone oil II and the remaining fumed silica and fumed titanium dioxide in batches, and mix at room temperature for 2 to 4 hours;

[0047] (2) After mixing is complete, the rubber material is heated to 150-180°C for heat treatment for 2-6 hours;

[0048] (3) Cool the rubber to room temperature and use a three-roll mill to grind it 3 to 5 times until the rubber is uniform and fine without agglomerated particles;

[0049] (4) According to the formula ratio, the dispersed rubber and methyl fluorosilicone oil are stirred and mixed, and the water is removed by vacuum, and then the fluorosilicone crosslinking agent, catalyst, and tackifier are added, and the vacuum is maintained and stirring is continued for 2 to 4 hours;

[0050] (5) Cooling the material to room temperature to obtain a high-strength room temperature vulcanized fluorosilicone sealant.

[0051] According to the present invention, preferably, the kneading treatment interval of each batch of materials in step (1) is 0.5 to 1 hour.

[0052] According to the present invention, preferably, the system pressure is maintained at -0.098 MPa during the heat treatment in step (2).

[0053] According to the present invention, preferably, in step (4), the dehydration time is 2 to 4 hours, and the dehydration pressure is -0.05 MPa to -0.09 MPa.

[0054] According to the present invention, the above-mentioned high-strength room temperature vulcanized fluorosilicone sealant is used in oil-resistant sealing materials.

[0055] Compared with the prior art, the technical features and beneficial effects of the present invention are as follows:

[0056] 1. The fluorosilicone crosslinking agent of the present invention is an acyloxysilane oligomer containing trifluoropropyl, and its molecular structure is well compatible with the fluorosilicone sealant system, avoiding the problem that conventional coupling agents such as methyltriacetoxysilane and vinyltriacetoxysilane are incompatible with the fluorosilicone system as crosslinking agents, and can be evenly dispersed in the rubber during the mixing of the formula. In addition, the crosslinking agent has high reactivity and can undergo efficient condensation reaction with the terminal hydroxyl group of the base rubber during room temperature vulcanization, so that the molecular chain segments are crosslinked more thoroughly, greatly improving the mechanical properties of the fluorosilicone sealant, especially the tensile strength.

[0057] 2. The present invention significantly improves the cross-linked network system of the fluorosilicone sealant by compounding high and low viscosity hydroxyl fluorosilicone oils, and then combines with a tackifier and methyl fluorosilicone oil. The synergistic effect of multiple materials allows the formed vulcanization system to intertwine with each other and form a stable dispersion state with the reinforcing filler, which can not only ensure the good mechanical properties of the fluorosilicone sealant, but also greatly reduce the viscosity of the rubber.

[0058] 3. The low-viscosity hydroxyl fluorosilicone oil in the present invention has a short molecular chain, which can not only be used as a building material for the rubber system, but also can well treat the silanol groups on the surface of the powder, playing the role of a structuring control agent. In addition, due to the presence of trifluoropropyl, the powder material and the fluorosilicone oil have good compatibility and can form a uniform system, thereby avoiding the thickening phenomenon of the sealant during storage and increasing the storage stability of the product.

[0059] 4. The fluorosilicone sealant of the present invention preferably combines fluorosilicone materials of various structures to have excellent oil resistance and bonding properties, and maintains good tolerance to various types of fuel, engine oil, etc. The oil resistance effect is very significant, and it can be used as an oil-resistant sealing material in multiple fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is the infrared spectrum of the fluorosilicone crosslinking agent prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0061] The present invention provides a high-strength room temperature vulcanized fluorosilicone sealant, a fluorosilicone crosslinking agent, and preparation and use thereof. The fluorosilicone crosslinking agent of the present invention is an acyloxysilane oligomer containing trifluoropropyl, and is well compatible with the fluorosilicone system.

[0062] In one or more preferred embodiments, the trifluoropropyl-containing acyloxysilane oligomer has a structure shown in formula (IV):

[0063]

[0064] In formula (IV), x represents the average degree of polymerization, and 1≤x≤3.

[0065] According to the present invention, the trifluoropropyl acyloxysilane oligomer having the structure shown in formula (IV) contains multiple acyloxy groups in its molecular structure and has high reaction activity. It can undergo efficient condensation reaction with the terminal hydroxyl groups of hydroxy fluorosilicone oil during room temperature vulcanization to make the molecular chain segments more thoroughly cross-linked. It can be used in the formulation of fluorosilicone sealants to greatly improve the mechanical properties of the fluorosilicone sealants.

[0066] According to the present invention, the preparation method of the above-mentioned fluorosilicone crosslinking agent comprises the following steps:

[0067] Under the protection of inert gas, anhydrous sodium acetate and toluene are stirred and mixed, heated to reflux to remove moisture, and then trifluoropropyltrichlorosilane is added dropwise to the system for acyl oxidation reaction. After the addition is completed, the reaction is continued to be stirred, and then the temperature is lowered, filtered, and the solvent is recovered to obtain a fluorosilicone crosslinking agent with a structure of formula (IV).

[0068] In one or more preferred embodiments, the molar ratio of trifluoropropyltrichlorosilane to anhydrous sodium acetate is 1:(3.1-3.3).

[0069] In one or more preferred embodiments, the feed mass ratio of anhydrous sodium acetate to toluene is 1:(2.0-4.0).

[0070] In one or more preferred embodiments, the time for removing moisture by heating and refluxing is 3 to 6 hours.

[0071] In one or more preferred embodiments, the acyl oxidation reaction temperature is 50-60°C.

[0072] In one or more preferred embodiments, the conditions for recovering the solvent are a temperature of 40 to 70° C. and a pressure of -0.04 MPa to -0.08 MPa.

[0073] According to the present invention, the trifluoropropyl-containing acyloxysilane oligomer of the structure represented by formula (IV) is used as a fluorosilicone crosslinking agent for the preparation of a room temperature vulcanized fluorosilicone sealant.

[0074] The high-strength room temperature vulcanized fluorosilicone sealant provided by the present invention significantly improves the cross-linked network system of the fluorosilicone sealant by compounding high and low viscosity hydroxyl fluorosilicone oils, and then cooperates with a tackifier and methyl fluorosilicone oil. The synergistic effect of multiple materials results in a fluorosilicone sealant with high strength, good tolerance to various types of fuels, engine oils, etc., and significant oil resistance. The sealant can be used as an oil-resistant sealing material in multiple fields.

[0075] According to the present invention, a high-strength room temperature vulcanized fluorosilicone sealant includes the above-mentioned fluorosilicone crosslinking agent and comprises the following components in parts by weight:

[0076] Hydroxyfluorosilicone oil I, 100 parts;

[0077] Fumed silica, 20-30 parts;

[0078] Fumed titanium dioxide, 10-20 parts;

[0079] Hydroxyfluorosilicone oil II, 3-10 parts;

[0080] Methyl fluorosilicone oil, 5-10 parts;

[0081] Fluorosilicone crosslinking agent, 5-10 parts;

[0082] Thickener, 1 to 3 parts;

[0083] Catalyst, 0.01-0.5 parts;

[0084] The hydroxy fluorosilicone oil I has a viscosity of 50,000 to 100,000 mPa.s and has a structure shown in formula (I):

[0085]

[0086] In formula (I), n represents the average degree of polymerization, 200≤n≤500;

[0087] The hydroxy fluorosilicone oil II has a viscosity of 100 to 150 mPa.s and has a structure shown in formula (II):

[0088]

[0089] In formula (II), m represents the average degree of polymerization, and 1≤m≤6.

[0090] In one or more preferred embodiments, the methyl fluorosilicone oil has a viscosity of 100 to 300 mPa.s and has a structure shown in formula (III):

[0091]

[0092] In formula (III), p represents the average degree of polymerization, and 1≤p≤10.

[0093] In one or more preferred embodiments, the tackifier is a mixture of tert-butyl alcohol and vinyl triacetoxysilane in a molar ratio of 2:1, which is obtained by alcoholysis and then desulfurization.

[0094] In one or more preferred embodiments, the alcoholysis reaction temperature of the tackifier is 30-40°C.

[0095] In one or more preferred embodiments, the stirring reaction temperature of the tackifier is 30-40° C., and the stirring time is 2-4 hours.

[0096] In one or more preferred embodiments, the conditions for the desaturation treatment of the tackifier are a temperature of 50 to 80° C. and a pressure of -0.09 MPa.

[0097] In one or more preferred embodiments, the tackifier is prepared as follows:

[0098] When vinyl triacetoxysilane is stirred and heated to 30-40°C, tert-butanol is added dropwise thereto for alcoholysis reaction. After the addition is completed, the stirring reaction is continued at 30-40°C. After the reaction is completed, the low molecular weight treatment is removed by maintaining the conditions of 50-80°C / -0.09MPa to obtain a thickener.

[0099] In one or more preferred embodiments, the catalyst is at least one of dibutyltin dilaurate, dibutyltin diacetate, stannous octoate, and dioctyltin dilaurate.

[0100] According to the present invention, the preparation method of the above-mentioned high-strength room temperature vulcanized fluorosilicone sealant comprises the following steps:

[0101] (1) Add hydroxy fluorosilicone oil I and part of fumed silica and fumed titanium dioxide into a vacuum kneader for kneading and mixing, then add hydroxy fluorosilicone oil II and the remaining fumed silica and fumed titanium dioxide in batches, and mix at room temperature for 2 to 4 hours;

[0102] (2) After mixing is complete, the rubber material is heated to 150-180°C for heat treatment for 2-6 hours;

[0103] (3) Cool the rubber to room temperature and use a three-roll mill to grind it 3 to 5 times until the rubber is uniform and fine without agglomerated particles;

[0104] (4) Add the dispersed rubber and methyl fluorosilicone oil into a planetary mixer according to the formula ratio, stir and mix, and remove moisture in a vacuum, then add the fluorosilicone crosslinking agent, catalyst, and tackifier, and continue stirring for 2 to 4 hours while maintaining the vacuum;

[0105] (5) Cooling the material to room temperature and sealing the material to obtain the high-strength room temperature vulcanized fluorosilicone sealant.

[0106] In one or more preferred embodiments, the kneading treatment interval of each batch of materials in step (1) is 0.5 to 1 hour.

[0107] In one or more preferred embodiments, the system pressure is maintained at -0.098 MPa during the heat treatment in step (2).

[0108] In one or more preferred embodiments, the dehydration time in step (4) is 2 to 4 hours, and the dehydration pressure is -0.05 MPa to -0.09 MPa.

[0109] According to the present invention, the above-mentioned high-strength room temperature vulcanized fluorosilicone sealant is used in oil-resistant sealing materials.

[0110] Anything not described in detail in the present invention is based on conventional techniques in the art.

[0111] The viscosities described in the examples are all viscosities at 25°C, and the room temperature described is 25±5°C.

[0112] The present invention will be further described below in conjunction with specific embodiments, which are not intended to limit the present invention.

[0113] The raw materials described in the examples are all conventional raw materials and can be purchased from the market or prepared according to the prior art.

[0114] The hydroxy fluorosilicone oil I used in the embodiment has a structure shown in formula (I):

[0115]

[0116] In formula (I), n represents the average degree of polymerization, and 200≤n≤500.

[0117] The hydroxy fluorosilicone oil II used has the structure shown in formula (II):

[0118]

[0119] In formula (II), m represents the average degree of polymerization, and 1≤m≤6.

[0120] The methyl fluorosilicone oil used has the structure shown in formula (III):

[0121]

[0122] In formula (III), p represents the average degree of polymerization, and 1≤p≤10.

[0123] The viscosity of the hydroxyfluorosilicone oil I is 50000-100000 mPa.s, the viscosity of the hydroxyfluorosilicone oil II is 100-150 mPa.s, and the viscosity of the methylfluorosilicone oil is 100-300 mPa.s.

[0124] The tackifier used in the examples was prepared by the following method:

[0125] Add 464g of vinyl triacetoxysilane to a reactor equipped with mechanical stirring, a thermometer, a reflux tube and a dropping funnel, start stirring and raise the temperature to 30-40°C, slowly add 296g of tert-butanol into the reactor for alcoholysis reaction. The reaction is exothermic during the addition process and the temperature is cooled by condensing brine. After the addition is completed, keep stirring at 30-40°C for 2h, and then maintain 50-80°C / -0.09MPa for desulfurization to obtain 387g of thickener.

[0126] Example 1

[0127] Fluorosilicone crosslinking agent, having a structure shown in formula (IV):

[0128]

[0129] In formula (IV), x represents the average degree of polymerization, and 1≤x≤3.

[0130] The preparation method of fluorosilicone crosslinking agent is as follows:

[0131] Under nitrogen protection, 1312g of anhydrous sodium acetate and 3936g of toluene were added to a reactor equipped with a mechanical stirrer, a thermometer, a reflux tube, and a dropping funnel. The mixture was stirred to form a suspension. The temperature was raised to 110°C and refluxed for 3h. The kettle temperature was then lowered to 50°C. 1157.5g of trifluoropropyltrichlorosilane was added dropwise to the kettle for acyl oxidation reaction. The reaction was exothermic during the addition. The kettle temperature was cooled by the jacket so that it did not exceed 60°C. After the addition was completed, 50-60°C was maintained and stirred for 3h. After the reaction was complete, the system was cooled to room temperature, the sodium chloride and excess sodium acetate generated by the reaction were filtered out, and the filtrate was collected. The solvent was evaporated and recovered at a temperature of 40-70°C and a pressure of -0.04MPa to -0.08MPa to obtain 1377g of fluorosilicone crosslinking agent with a viscosity of 13mPa.s and a yield of 91.2%.

[0132] The infrared spectrum of the fluorosilicone crosslinking agent prepared above is as follows: Figure 1 As shown, 1739cm -1 The strong peak at 1201 cm is the typical characteristic absorption peak of Si-OCOCH3. -1 The peak at 1371 cm is the characteristic absorption peak of the CF bond in Si-CH2CH2CF3. -1 The peak at 1257 cm is the bending vibration absorption peak of Si-C bond. -1 The peak at 1319 cm is the deformation vibration absorption peak of Si-C bond. -1 The peak at 900cm is the absorption peak of the CC bond in -CH2-CH2- -1 The peak at is the absorption peak of the CC bond in -CH2-CF3. The data characterized by this spectrum can indicate the structure of the product.

[0133] Example 2

[0134] The preparation of a high-strength room temperature vulcanized fluorosilicone sealant, including the use of the fluorosilicone crosslinking agent described in Example 1, comprises the following steps:

[0135] (1) Add 1000 g of hydroxy fluorosilicone oil I (viscosity 64000 mPa.s), 50 g of fumed silica (specific surface area 200 m 2 / g), 25g fumed titanium dioxide (specific surface area 50m 2 / g) and kneaded and mixed for 0.5h, and then the remaining 150g of fumed silica, 75g of fumed titanium dioxide and 80g of hydroxy fluorosilicone oil II (viscosity 140mPa.s) were added to the kneader in three batches, with a kneading interval of 0.5h for each batch. After all the materials were added, kneading and mixing were continued at room temperature for 2h;

[0136] (2) After mixing is complete, turn on the heating and heat the rubber material to 180°C for heat treatment for 3 hours. During the heat treatment, the system pressure is maintained at -0.098 MPa;

[0137] (3) Cool the rubber to room temperature and continue to grind it through a three-roll mill for 3 to 5 times until the rubber is uniform and fine without visible agglomerated particles;

[0138] (4) Add the thinned rubber into a planetary mixer, then add 50 g of methyl fluorosilicone oil (viscosity 150 mPa.s) and stir for 2 h while removing moisture under vacuum, then add 80 g of fluorosilicone crosslinking agent of formula (IV), 10 g of tackifier and 1 g of dibutyltin dilaurate into the kettle, and continue stirring for 3 h while maintaining vacuum conditions;

[0139] (5) The material is cooled to room temperature and sealed in a plastic barrel to obtain the high-strength room temperature vulcanized fluorosilicone sealant.

[0140] The obtained fluorosilicone sealant was cured for 7 days at 23° C. and 50% relative humidity to prepare a 2 mm standard test piece. The test piece was tested for mechanical properties. The results are shown in Table 1. The test piece was tested for oil resistance. The results are shown in Table 2.

[0141] Example 3

[0142] The preparation of a high-strength room temperature vulcanized fluorosilicone sealant, including the use of the fluorosilicone crosslinking agent described in Example 1, comprises the following steps:

[0143] (1) Add 1000 g of hydroxy fluorosilicone oil I (viscosity 64000 mPa.s), 50 g of fumed silica (specific surface area 200 m 2 / g), 25g fumed titanium dioxide (specific surface area 50m 2 / g) and kneaded and mixed for 0.5h, and then the remaining 150g of fumed silica, 75g of fumed titanium dioxide and 100g of hydroxy fluorosilicone oil II (viscosity 140mPa.s) were added to the kneader in three batches, with a kneading interval of 0.5h for each batch. After all the materials were added, kneading and mixing were continued at room temperature for 2h;

[0144] (2) After mixing is complete, turn on the heating and heat the rubber material to 180°C for heat treatment for 3 hours. During the heat treatment, the system pressure is maintained at -0.098 MPa;

[0145] (3) Cool the rubber to room temperature and continue to grind it through a three-roll mill for 3 to 5 times until the rubber is uniform and fine without visible agglomerated particles;

[0146] (4) Add the thinned rubber into a planetary mixer, then add 60 g of methyl fluorosilicone oil (viscosity 150 mPa.s) and stir for 2 h while removing moisture under vacuum, then add 90 g of fluorosilicone crosslinking agent of formula (IV), 15 g of tackifier and 1.2 g of dibutyltin dilaurate into the kettle, and continue stirring for 3 h while maintaining vacuum conditions;

[0147] (5) The material is cooled to room temperature and sealed in a plastic barrel to obtain the high-strength room temperature vulcanized fluorosilicone sealant.

[0148] The obtained fluorosilicone sealant was cured for 7 days at 23° C. and 50% relative humidity to prepare a 2 mm standard test piece. The test piece was tested for mechanical properties. The results are shown in Table 1. The test piece was tested for oil resistance. The results are shown in Table 2.

[0149] Example 4

[0150] The preparation of a high-strength room temperature vulcanized fluorosilicone sealant, including the use of the fluorosilicone crosslinking agent described in Example 1, comprises the following steps:

[0151] (1) Add 1000 g of hydroxy fluorosilicone oil I (viscosity 64000 mPa.s), 55 g of fumed silica (specific surface area 200 m 2 / g), 30g fumed titanium dioxide (specific surface area 50m 2 / g) and kneaded and mixed for 0.5h, and then the remaining 165g of fumed silica, 100g of fumed titanium dioxide and 100g of hydroxy fluorosilicone oil II (viscosity 140mPa.s) were added to the kneader in three batches, with a kneading interval of 0.5h for each batch. After all the materials were added, kneading and mixing were continued at room temperature for 2h;

[0152] (2) After mixing is complete, turn on the heating and heat the rubber material to 180°C for heat treatment for 3 hours. During the heat treatment, the system pressure is maintained at -0.098 MPa;

[0153] (3) Cool the rubber to room temperature and continue to grind it through a three-roll mill for 3 to 5 times until the rubber is uniform and fine without visible agglomerated particles;

[0154] (4) Add the thinned rubber into a planetary mixer, then add 50 g of methyl fluorosilicone oil (viscosity 150 mPa.s) and stir for 2 h while removing moisture under vacuum, then add 90 g of fluorosilicone crosslinking agent of formula (IV), 15 g of tackifier and 1.2 g of dibutyltin dilaurate into the kettle, and continue stirring for 3 h while maintaining vacuum conditions;

[0155] (5) The material is cooled to room temperature and sealed in a plastic barrel to obtain the high-strength room temperature vulcanized fluorosilicone sealant.

[0156] The obtained fluorosilicone sealant was cured for 7 days at 23° C. and 50% relative humidity to prepare a 2 mm standard test piece. The test piece was tested for mechanical properties. The results are shown in Table 1. The test piece was tested for oil resistance. The results are shown in Table 2.

[0157] Example 5

[0158] The preparation of a high-strength room temperature vulcanized fluorosilicone sealant, including the use of the fluorosilicone crosslinking agent described in Example 1, comprises the following steps:

[0159] (1) Add 1000 g of hydroxy fluorosilicone oil I (viscosity 64000 mPa.s), 55 g of fumed silica (specific surface area 200 m 2 / g), 30g fumed titanium dioxide (specific surface area 50m 2 / g) and kneaded and mixed for 0.5h, and then the remaining 165g of fumed silica, 100g of fumed titanium dioxide and 80g of hydroxy fluorosilicone oil II (viscosity 140mPa.s) were added to the kneader in three batches, with a kneading interval of 0.5h for each batch. After all the materials were added, kneading and mixing were continued at room temperature for 2h;

[0160] (2) After mixing is complete, turn on the heating and heat the rubber material to 180°C for heat treatment for 3 hours. During the heat treatment, the system pressure is maintained at -0.098 MPa;

[0161] (3) Cool the rubber to room temperature and continue to grind it through a three-roll mill for 3 to 5 times until the rubber is uniform and fine without visible agglomerated particles;

[0162] (4) Add the thinned rubber into a planetary mixer, then add 70 g of methyl fluorosilicone oil (viscosity 150 mPa.s) and stir for 2 h while removing moisture under vacuum, then add 70 g of fluorosilicone crosslinking agent of formula (IV), 10 g of tackifier and 1 g of dibutyltin dilaurate into the kettle, and continue stirring for 3 h while maintaining vacuum conditions;

[0163] (5) The material is cooled to room temperature and sealed in a plastic barrel to obtain the high-strength room temperature vulcanized fluorosilicone sealant.

[0164] The obtained fluorosilicone sealant was cured for 7 days at 23° C. and 50% relative humidity to prepare a 2 mm standard test piece. The test piece was tested for mechanical properties. The results are shown in Table 1. The test piece was tested for oil resistance. The results are shown in Table 2.

[0165] Comparative Example 1

[0166] The preparation method of Example 2 of the present invention was repeated, except that the fluorosilicone crosslinking agent of formula (IV) was replaced by methyltriacetoxysilane, and the amounts of other materials and the operating steps remained unchanged.

[0167] The obtained fluorosilicone sealant was cured for 7 days at 23° C. and 50% relative humidity to prepare a 2 mm standard test piece. The mechanical properties of the test piece were tested. The results are shown in Table 1.

[0168] Comparative Example 2

[0169] The preparation method of Example 2 of the present invention was repeated, except that the fluorosilicone crosslinking agent of formula (IV) was replaced by vinyl triacetoxysilane, and the amounts of other materials and the operating steps remained unchanged.

[0170] The obtained fluorosilicone sealant was cured for 7 days at 23° C. and 50% relative humidity to prepare a 2 mm standard test piece. The mechanical properties of the test piece were tested. The results are shown in Table 1.

[0171] Comparative Example 3

[0172] The preparation method of Example 2 of the present invention was repeated, except that the hydroxyfluorosilicone oil II was removed, and the feeding amounts of other materials and the operation steps remained unchanged.

[0173] When the materials are kneaded and mixed by a kneading machine, it can be found that the viscosity of the rubber material in Comparative Example 3 is significantly increased compared with that in Example 2, and the powder is difficult to be evenly dispersed in the system. The rubber material is viscous, stiff, and non-thixotropic. In the subsequent formulation preparation process, the crosslinking agent, tackifier, catalyst, etc. are also difficult to mix in the system. Even if the speed of the planetary mixer is increased, the effect is not ideal. In addition, the rubber material will slowly thicken during storage and gradually lose its processing performance, and cannot be used to prepare fluorosilicone sealants.

[0174] Test example

[0175] The fluorosilicone sealants prepared in Examples 2 to 5 and Comparative Examples 1 to 2 were tested for mechanical properties and oil resistance, and the test results are shown in Tables 1 and 2. Among them, the density was tested according to ASTM D792; the hardness was tested according to ASTM D2240; the tensile strength and elongation at break were tested according to ASTM D412; the tear strength was tested according to ASTM D624B; the peel strength was tested according to GB / T 15254; the surface drying time was tested according to GB / T 13477.5; the oil resistance was tested according to ASTM D471; the viscosity test was performed using a German HAAKE VTiQ intelligent rheometer, and the test method was: 20 mm flat rotor, shear rate 10 s -1 , tested at 25℃ for 50 seconds.

[0176] Table 1

[0177]

[0178] Table 2

[0179] Oil resistance Example 2 Example 3 Example 4 Example 5 IRM903, ΔV / % (150℃×168h) 1.5 1.1 1.4 1.2 RP-3 aviation kerosene, ΔV / % (60℃×168h) 3.9 3.9 4.2 4.0 0# diesel, ΔV / % (60℃×168h) 2.3 2.0 2.4 2.5 Fuel C, ΔV / % (60℃×168h) 19.7 19.6 19.4 19.1 FAM B, ΔV / % (60℃×168h) 28.0 29.0 27.7 28.2

[0180] As shown in Table 1 and Table 2, the high-strength fluorosilicone sealant prepared by the method described in Examples 2 to 5 of the present invention has excellent mechanical properties, especially tensile strength exceeding 4MPa, low viscosity, good thixotropy, strong adhesion, and high reactivity at room temperature. In addition, the fluorosilicone sealant also has excellent oil resistance, maintains good tolerance to various test oils, and has a very significant oil resistance effect, and can be used as an oil-resistant sealing material in multiple fields.

[0181] Comparative Example 1 uses methyl triacetoxysilane as a crosslinking agent. Due to its high melting point (about 40°C), it needs to be melted before use. The rubber compound prepared with it has the risk of crystallization during storage, which affects the product quality and storage stability. In addition, due to its incompatibility with the fluorosilicone system, the prepared fluorosilicone sealant has poor performance and cannot be used as a high-strength sealing material.

[0182] Comparative Example 2 uses vinyl triacetoxysilane as a crosslinking agent. Also due to system compatibility issues, the strength of the product is very low, and the viscosity of the rubber is high, the operation time is short, the construction is difficult, and it has no use value.

[0183] The technical contents and features of the present invention are as shown above, but the protection scope of the present invention should not be limited to the contents described in the embodiments, but should include various replacements and modifications that do not deviate from the present invention and are covered by the claims of the present invention.

Claims

1. A fluorosilicone crosslinking agent, characterized in that: The fluorosilicone crosslinking agent is an acyloxysilane oligomer containing a trifluoropropyl group.

2. The fluorosilicone crosslinking agent according to claim 1, characterized in that The trifluoropropyl-containing acyloxysilane oligomer has a structure shown in formula (IV): In formula (IV), x represents the average degree of polymerization, and 1≤x≤3.

3. The method for preparing the fluorosilicone crosslinking agent according to claim 1, comprising the following steps: Under the protection of inert gas, anhydrous sodium acetate and toluene are stirred and mixed, heated to reflux to remove moisture, and then trifluoropropyltrichlorosilane is added dropwise to the system for acyl oxidation reaction. After the addition is completed, the reaction is continued to be stirred, and then the temperature is lowered, filtered, and the solvent is recovered to obtain a fluorosilicone crosslinking agent.

4. The method for preparing a fluorosilicone crosslinking agent according to claim 3, characterized in that: The molar ratio of trifluoropropyltrichlorosilane to anhydrous sodium acetate is 1:(3.1-3.3); Preferably, the mass ratio of anhydrous sodium acetate to toluene is 1:(2.0-4.0); Preferably, the time for removing moisture by heating and refluxing is 3 to 6 hours; Preferably, the acyl oxidation reaction temperature is 50-60°C; Preferably, the conditions for recovering the solvent are a temperature of 40 to 70° C. and a pressure of -0.04 MPa to -0.08 MPa.

5. The trifluoropropyl-containing acyloxysilane oligomer according to claim 2 is used as a fluorosilicone crosslinking agent for the preparation of a room temperature vulcanized fluorosilicone sealant.

6. A high-strength room temperature vulcanized fluorosilicone sealant, comprising the fluorosilicone crosslinking agent according to claim 1 or 2, characterized in that: By weight, it includes the following components: Hydroxyfluorosilicone oil I, 100 parts; Fumed silica, 20-30 parts; Fumed titanium dioxide, 10-20 parts; Hydroxyfluorosilicone oil II, 3-10 parts; Methyl fluorosilicone oil, 5-10 parts; Fluorosilicone crosslinking agent, 5-10 parts; Thickener, 1 to 3 parts; Catalyst, 0.01-0.5 parts; The hydroxy fluorosilicone oil I has a viscosity of 50,000 to 100,000 mPa.s and has a structure shown in formula (I): In formula (I), n represents the average degree of polymerization, 200≤n≤500; The hydroxy fluorosilicone oil II has a viscosity of 100 to 150 mPa.s and has a structure shown in formula (II): In formula (II), m represents the average degree of polymerization, and 1≤m≤6.

7. The high-strength room temperature vulcanized fluorosilicone sealant according to claim 6, characterized in that: The methyl fluorosilicone oil has a viscosity of 100 to 300 mPa.s and has a structure shown in formula (III): In formula (III), p represents the average degree of polymerization, 1≤p≤10; Preferably, the BET specific surface area of ​​the fumed silica is 175 to 225 m 2 / g; Preferably, the BET specific surface area of ​​the vapor phase titanium dioxide is 35 to 65 m 2 / g. Preferably, the tackifier is a mixture of tert-butyl alcohol and vinyl triacetoxysilane in a molar ratio of 2:1, after alcoholysis reaction and then removal of low molecular weight treatment; Preferably, the catalyst is at least one of dibutyltin dilaurate, dibutyltin diacetate, stannous octoate and dioctyltin dilaurate.

8. The method for preparing the high-strength room temperature vulcanized fluorosilicone sealant according to claim 6 or 7, comprising the following steps: (1) Add hydroxy fluorosilicone oil I and part of fumed silica and fumed titanium dioxide into a vacuum kneader for kneading and mixing, then add hydroxy fluorosilicone oil II and the remaining fumed silica and fumed titanium dioxide in batches, and mix at room temperature for 2 to 4 hours; (2) After mixing is complete, the rubber material is heated to 150-180°C for heat treatment for 2-6 hours; (3) Cool the rubber to room temperature and use a three-roll mill to grind it 3 to 5 times until the rubber is uniform and fine without agglomerated particles; (4) According to the formula ratio, the dispersed rubber and methyl fluorosilicone oil are stirred and mixed, and the water is removed by vacuum, and then the fluorosilicone crosslinking agent, catalyst, and tackifier are added, and the vacuum is maintained and stirring is continued for 2 to 4 hours; (5) Cooling the material to room temperature to obtain a high-strength room temperature vulcanized fluorosilicone sealant.

9. The method for preparing the high-strength room temperature vulcanized fluorosilicone sealant according to claim 8, characterized in that: The kneading treatment interval of each batch of materials in step (1) is 0.5 to 1 hour; Preferably, the system pressure is maintained at -0.098 MPa during the heat treatment in step (2); Preferably, in step (4), the dehydration time is 2 to 4 hours, and the dehydration pressure is -0.05 MPa to -0.09 MPa.

10. Use of the high-strength room temperature vulcanized fluorosilicone sealant according to claim 6 or 7 in oil-resistant sealing materials.

Citation Information

Patent Citations

  • Single-component room-temperature-vulcanized fluorosilicone rubber and preparation method thereof

    CN102850807A

  • Fluorine-silicon sealant for fuel oil-resisting solvent part and preparation method for fluorine-silicon sealant

    CN105086473A

  • Room temperature vulcanized fluorosilicone rubber and preparation method thereof

    CN110577747A

  • Engine oil-resistant low-pressure-change addition type liquid fluorinated silicone rubber and preparation method thereof

    CN114456605A

  • Fluorosilicone pouring sealant and preparation method thereof

    CN115975597A